KAJIAN EKOTEOLOGI TERHADAP KERUSAKAN LINGKUNGAN DI KOTA RANTEPAO BERDASARKAN KEJADIAN 1:28 SERTA KAITANNYA DENGAN FALSAFAH TALLU LOLONA - Dzulkifli Sanjani; Megayanty Yoland. S; Robiyanto Sultra M (ADISAM PUBLISHER, 2023)
This study aims to read the behavior of the Toraja people in the perspective of Genesis 1:28 in environmental care and to find out the causes of the lack of awereness of the Toraja people in treating the environment in the city of Rantepao. This paper aims to show the relationship between humans and nature in building a contextual ecotheology of Toraja society. This study uses a descriptive qualitative approach. The informants in this study are the people who live in Rantepao. In this study it was found that the lack of public awereness in protecting the environment was caused by a misunderstanding in reading the text of Genesis 1:28, and the waning of the philosophical values of tallu lolona in the Toraja community. Environtmental damage, which is commonly known as the ecological crisis, is a problem that cannot be left unattended because the continuous occurrence of ecological crises in the world can have a very serious impact on the balance and sustainability of living beings life. In the culture of the Toraja people, the philosophy of tallu lolona is an illustration of how the Toraja peple have a harmonious relationship between humans and other God’s creation, namely the philosophy of tallu lolona describing the life of the Toraja people who view God’s creation equally.